A comparative study of polycaprolactone–hydroxyapatite scaffold and collagen membrane carriers for recombinant human bone morphogenic protein-2 for guided bone regeneration. Issue 1 (2nd January 2022) - Rittipakorn, Pawornwan; Thuaksuban, Nuttawut; Mai-ngam, Katanchalee; Charoenla, Satrawut
Abstract: The polycaprolactone-30% hydroxyapatite (PCL-30%HA) scaffolds were fabricated using Melt Stretching and Multilayer Deposition (MSMD) technique. Different models of guided bone regeneration were evaluated in rat models. Group A, the calvarial defects were covered with collagen membranes. Group B, the scaffolds were placed into the defects and covered with the membranes. 200 µL of the 400 µg/mL BMP solution was slowly dripped onto the membranes. Group C, the scaffolds were soaked in the BMP solution before being placed. Group D, only the scaffolds were placed. Conclusively, the Group C model could enhance new bone formation better than the other models. Graphical Abstract: UF0001